Book Review: Geological Excursions Around Miri, Sarawak 1910-2010 Celebrating The 100th Anniversary of the Discovery of The Miri Oil Field - Herman Darman (Berita Sedimentologi, 2011)
Geological Excursions Around Miri, Sarawak1910-2010 Celebrating The 100th Anniversary of the Discovery of The Miri Oil FieldAuthors:Mario Wannier, Philip Lesslar, Charlie Lee, Han Raven, Rasoul Sorkhabi, Abdullah IbrahimPublished in 2011